Glycan-decorated HPMA copolymers as high-affinity lectin ligands. Issue 17 (10th April 2017) - Bojarová, P.; Chytil, P.; Mikulová, B.; Bumba, L.; Konefał, R.; Pelantová, H.; Krejzová, J.; Slámová, K.; Petrásková, L.; Kotrchová, L.; Cvačka, J.; Etrych, T.; et al.
Abstract : New conjugates of N -(2-hydroxypropyl) methacrylamide (HPMA) copolymers tethered with chitooligosaccharidic epitopes of varying lengths are potent ligands of wheat germ agglutinin, reaching subnanomolar binding affinities. Abstract : Novel conjugates of N -(2-hydroxypropyl) methacrylamide (HPMA) copolymers tethered with chitooligosaccharidic epitopes of varying lengths were shown to be potent ligands of a model lectin, wheat germ agglutinin (WGA). The azide-functionalized oligosaccharidic epitopes were prepared by the action of Tyr470Asn mutant β- N -acetylhexosaminidase from Talaromyces flavus in a single reaction step and were conjugated to HPMA copolymer precursors in a defined pattern and density through Cu + -catalyzed azide–alkyne cycloaddition. The soluble, biocompatible, and structurally flexible synthetic glycopolymers were studied for their binding to WGA in a competitive enzyme-linked lectin assay (ELLA), and the kinetics of interaction were analyzed by surface plasmon resonance (SPR). To the best of our knowledge, this study presents the first HPMA copolymers derivatized with long oligosaccharides that demonstrate high affinity to a lectin target. The binding affinities in the low nanomolar and subnanomolar ranges place the prepared glycopolymers among the best WGA ligands reported to date. This study demonstrates the targeting potential of these glycopolymers for therapeutically relevant lectins.